Igneous Rock Associations of Canada 2. Stages in the Temporal Evolution of Calderas - Kennedy, Ben; Stix, John (Geoscience Canada, 2003)
Summary This paper combines the temporal model of caldera formation presented by Robert Smith and Roy Bailey in 1968 with recent volcanological concepts. Field examples, experimental models and theoretical studies are synthesized toillustrate the process of caldera collapse conceptually as a series of stages of eruption and deformation. During each stage, physical changes occur at the surface, within the underlying magma chamber, and within the subsiding block or blocks that lie between the surface and the top of the magma chamber. The stages are as follows: 1) magma chamber intrusion, 2) initial eruption, down sagging and the on set of subsidence, 3) main subsidence and eruption phase, 4) peripheral extension and eruption quiescence, 5) continued eruption, subsidence and change oferuptive style, and 6) resurgence and extrusion of lava domes and flows. These stages may then be repeated as a subsequent caldera cycle. Every caldera has an individual history and may deform in a different manner at each stage. The paper outlines how these stages can give rise to different caldera types.